IL-6 and TNF-α serum levels are associated with early death in community-acquired pneumonia patients - M.R. Bacci; R.C.P. Leme; N.P.C. Zing; N. Murad; F. Adami; P.F. Hinnig; D. Feder; A.C.P. Chagas; F.L.A. Fonseca (Brazilian Journal of Medical and Biological Research, 2015)
Community-acquired pneumonia (CAP) is amongst the leading causes of death worldwide. As inflammatory markers, cytokines can predict outcomes, if interpreted together with clinical data and scoring systems such as CURB-65, CRB, and Acute Physiology and Chronic Health Evaluation II (APACHE II). The aim of this study was to determine the impact of inflammatory biomarkers on the early mortality of hospitalized CAP patients. Twenty-seven CAP patients needing hospitalization were enrolled for the study and samples of interleukin-1 (IL-1) and interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), C-reactive protein (CRP), and homocystein were collected at the time of admission (day 1) as well as on the seventh day of the treatment. There was a significant reduction in the levels of IL-6 between the first and the second collections. Median IL-6 values decreased from 24 pg/mL (day 1) to 8 pg/mL (day 7) (P=0.016). The median levels of TNF-α were higher in patients: i) with acute kidney injury (AKI) (P=0.045), ii) requiring mechanical ventilation (P=0.040), iii) with short hospital stays (P=0.009), iv) admitted to the intensive care unit (ICU) (P=0.040), v) who died early (P=0.003), and vi) with worse CRB scores (P=0.013). In summary, IL-6 and TNF-α levels were associated with early mortality of CAP patients. Longer admission levels demonstrated greater likelihood of early death and overall mortality, necessity of mechanical ventilation, and AKI.